Distribuição espacial, composição taxonômica e diversidade funcional de copepoda em águas doces do estado de São Paulo - Duarte, Matheus Almeida (2021)
Copepods are important components of freshwater zooplankton, acting as a connection between communities, feeding on small microorganisms, algae and other invertebrates and themselves serving as food for similar invertebrates, aquatic insects, and especially fish in the upper trophic levels. They are vulnerable to anthropic actions, particularly to eutrophication, which causes a decrease in species richness, derregulation and interruption of reproductive cycles, besides potential species extinction. This group was selected for the present study as an indicator group of the effects of this process on the freshwater biota from São Paulo State. During the period from 2011 to 2015, 300 water bodies were sampled in the 22 Water Resources Management Units in the state. A semi-quantitative sampling was carried out, with 5 horizontal trawls of the plankton net in the shallow systems and combined horizontal and vertical in the deep ones. Copepods occurred in 280 bodies of water in 22 UGHRIs. A total of 36 species were recorded, 10 species of Calanoida, 26 of Cyclopoida and juveniles of Harpacticoida. The most representative genera in number of species were Notodiaptomus (Calanoida) and Mesocyclops (Cyclopoida). The most widely distributed species were Thermocyclops decipiens, Tropocyclops prasinus and Notodiaptomus deitersi. The highest population densities were found for Thermocyclops decipiens, Thermocyclops minutus and Notodiaptomus iheringi. Analysis of the relationship between species richness, uniformity, taxonomic and functional diversity and the trophic status of water bodies revealed that Copepoda have greatest species diversity in oligotrophic systems. As eutrophication progresses, all these variables decrease. The data obtained by the indicator species index points to a set of indicator species that can be selected and used in future studies to monitor changes in the distribution of these species in São Paulo State or in other regions of the country. Analysis of eutrophication effects on taxonomic and functional diversity of Copepoda, that is, on the variety of “ecological roles” of species, revealed that for both components evaluated, functional equitability and functional diversity, there were negatively correlations with the degree of eutrophication of the water bodies. Thus, it was concluded that taxonomic and functional diversity decrease as freshwaters become increasingly eutrophicated and, therefore, the conservation of aquatic biodiversity will depend on control or the revertion of this process.